Pengaruh umur perusahaan, profitabilitas, dan thin capitalization terhadap tax avoidance - Putri, Yadiva Nicauri Herning; Hasanah, Nuramalia; Nasution, Hafifah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
One of the burdens that is considered to be a consideration for companies to minimize is the tax burden. This study investigates the effect of company age, profitability, and thin capitalization on tax avoidance practices. Conducted on consumer non-cyclicals sector companies listed on the IDX (2020-2022). Purposive sampling technique with this type of quantitative resulted in 125 observations after excluding outlier data. Analysis using multiple linear regression. The results show that only profitability has a significant effect on tax avoidance. Company age and thin capitalization are not significant in this company context. The discovery can contribute to a deeper comprehension of the various factors that shape tax avoidance practices within the industry. These findings underscores the significance of taking into account key factors such as company age, profitability, and thin capitalization when formulating effective tax strategies. By gaining a deeper understanding of the intricate connection between these factors and tax avoidance practices, it becomes possible to enhance tax compliance measures and address any vulnerabilities or gaps in existing tax regulations.